Induced Corneal Ulcers in Cats - Effects of 2% Dorzolamide on Epithelization Time and on the Expression of Matrix Metalloproteinase-9 - Dumit Pizzinatto, Fabio; Ribeiro, Alexandre; Carvalho Silveira, Bruna; Moraes Lobo, Paloma; Rodrigues Miranda, Hanna; Assis Pereira, Nathalia (Acta Scientiae Veterinariae, 2023)
Background: Topically administered 2% dorzolamide is among the most commonly used agents to lower IOP. As a complication of glaucoma, blind patients may develop corneal ulcers secondary to trauma. Nonetheless, in patients with a hypertensive or glaucomatous eye, in which the cornea has also been ulcerated, medical hypotensive therapy should not be discontinued. Therefore, the present study aimed to determine whether the instillation of a benzalkonium chloride (BAK)-preserved 2% dorzolamide alters corneal wound healing time and the levels of matrix metalloproteinases (MMP-9) in the tears of cats with experimentally induced corneal ulcers. Materials, Methods & Results: Sixteen cats (8/group) were randomly assigned to receive 40 µL of 2% dorzolamide (TG) or saline (CG) 3 times daily until corneal re-epithelialization. Experimental keratectomies were performed under general and topical anesthesia using an operating microscope. For this purpose, a millimitred trephine was calibrated and used to create a temporal paraxial corneal ulcer with a diameter of 6 mm and a depth of 200 µm. After corneal wounding, the ulcerated area, the healing time, blepharospasm, conjunctival hyperemia, and aqueous flare were compared between groups. Tears were collected at baseline and 24 and 48 h after keratectomy, and the total MMP-9 was quantified by ELISA. Data were assessed statistically using unpaired Student’s t test, one-way, and two-way ANOVA followed by a Bonferroni post hoc test. Statistical significance was set at P < 0.05 for all analyses. The average time to achieve corneal wound healing did not differ between groups (P = 0.36) and was 65.50 ± 3.62 h in the CG and 71.00 ± 4.58 h in the TG. Twenty-four h after keratectomy, the ulcerated area in the CG was 3.34 mm2 larger than that observed in the TG (P = 0.04); the rest of the comparisons did not reach statistical significance at any time point between groups (P > 0.05). Higher blepharospasm scores were observed in cats of TG (P = 0.04). When compared with baseline of both groups, the levels of MMP-9 increased significantly at 24 and 48 h post-keratectomy (P < 0.001), but differences between groups were not observed at 24 and 48 h post-keratectomy (P > 0.05). Discussion: In cats, 9 mm axial corneal ulcers created by superficial debridement re-epithelize approximately 48 h post-wounding. In the present study, re-epithelialization post keratectomy occurred within an average time of 68.25 h in most cats and in a delayed manner in one cat of the TG after 96 h. In the current study, the lesions in both groups healed without corneal scarring, pigmentation, or vascularization. Although BAC was present in all topical medications used in the present study, the authors attribute the higher scores of blepharospasm in the TG to the rheological characteristics and the pH of the dorzolamide ophthalmic solution. Indeed, the pH value of dorzolamide (5.58) may cause signs of irritation, as the tear film has an approximate pH of 7.6. Previous studies showed that ulcerated corneas presented significantly higher levels of MMP-9 in tears at the early stages (8 to 36 h) post-wounding. In the current study, the levels of this enzyme after wounding did not change significantly in the tears of cats treated with 2% dorzolamide when compared to the eyes in the control group. This study showed that the instillation of a BAC-preserved 2% dorzolamide ophthalmic solution did not impair the corneal wound healing time or the early expression of MMP-9 in the tears of cats with experimentally induced corneal ulcers. However, our results warrant further investigation in patients with ocular hypertension or glaucoma presenting concomitant naturally occurring corneal ulcers to certify our findings. Keywords: carbonic anhydrase inhibitor, benzalkonium chloride, ulcerative keratitis, corneal healing, glaucoma.